STUDY OF TEACHER PREPAREDNESS IN FACING FLOOD DISASTERS AT SMA N 1 PERHENTIAN RAJA RIAU PROVINCE - Resti Yolanda Putri; Dedi Hermon (GeoEco)
A flood disaster is one of the disasters that can cause severe damage in the occurrence of floods because, in addition to causing property damage, flash floods can also cause loss of life. Floods are a disaster that often occurs in Indonesia, and Kampar Regency in Riau Province is one of the most affected areas. Therefore, it is important for all levels of society to adequately prepare to deal with the potential consequences of the flood disaster. This study was conducted with three main objectives, namely: first, to analyze the impact of floods; second, to analyze the level of teacher preparedness in dealing with floods; and third, to formulate a teacher preparedness strategy in dealing with floods at SMA Negeri 1 Perhentian Raja, Kampar Regency, Riau Province. Data were collected using interviews and questionnaires, in addition to AHP analysis. A mixed-method approach was used in this study. The study results indicate that the consequences of the flood disaster at SMA Negeri 1 Perhentian Raja include losses and damage to existing facilities and infrastructure. In addition, the level of teacher preparedness in dealing with floods hampers the learning process and damages school facilities and infrastructure. Regarding teacher preparedness in facing flood disasters, it can be classified into the 'ready' category. Based on the AHP analysis of teacher preparedness strategies in facing flood disasters, there are five alternatives that are the main priorities for teachers at SMA Negeri 1 Perhentian Raja, Kampar Regency, Riau Province.